Tobacco Tax Reform at the Crossroads of Health and Development : A Multisectoral Perspective - Marquez, Patricio V.; Moreno-Dodson, Blanca (World Bank, Washington, DC, 2017)
There is a policy measure that can simultaneously save millions of lives, reduce poverty, and increase countries’ domestic resources for financing development. The policy measure consists of increasing excise tax rates on tobacco in order to reduce its affordability and, as evidence shows, lower its consumption. Today, this powerful human development and poverty reduction measure remains largely underutilized, especially in low- and middle-income countries (LMICs). This report provides decision support for policy makers on tobacco tax reform, as well as analytical and empirical tools for using tobacco excise taxes to save lives and increase government revenues. The report sets forth the public health, economic, and anti-poverty case for higher tobacco taxes; shows how some countries have already delivered ambitious reforms; and documents measurable results. It shows that, by implementing tobacco tax reforms now, policy makers can choose a fast road to healthier, more prosperous societies.